Enrichment techniques employed in phosphoproteomics - Fíla, Jan (Springer Vienna, 2011)
Rapid changes of protein phosphorylation play a crucial role in the regulation of many cellular processes. Being post-translationally modified, phosphoproteins are often present in quite low abundance and tend to co-exist with their unphosphorylated isoform within the cell. To make their identification more practicable, the use of enrichment protocols is often required. The enrichment strategies can be performed either at the level of phosphoproteins or at the level of phosphopeptides. Both approaches have their advantages and disadvantages. Most enriching strategies are based on chemical modifications, affinity chromatography to capture peptides and proteins containing negatively charged phosphate groups onto a positively charged matrix, or immunoprecipitation by phospho-specific antibodies. In this article, the most up-to-date enrichment techniques are discussed, taking into account their optimization, and highlighting their advantages and disadvantages. Moreover, these methods are compared to each other, revealing their complementary nature in providing comprehensive coverage of the phosphoproteome.